The Natural World and Science Education in the United States - Sharma, Ajay (Springer International Publishing, 2018)
This book focuses on the representation of nature in science education in schools in the United States. Given the importance of our relationship with the nonhuman world for the fate of our planet, this work gives special attention to the representation, instruction, and understanding of the relationship between the social and the natural world. It also proposes an alternative, sustainability science-based conceptual framework for ecology and environmental science topics in science education, which is compatible with the current social-ecological understanding of life in the Anthropocene epoch.